2019
DOI: 10.1038/s41577-019-0139-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism and natural killer cell responses

Abstract: Natural killer (NK) cells are lymphocytes with important roles for innate and adaptive immune responses to tumours and viral infection. However, in certain chronic diseases, including obesity and cancer, NK cells are found to have impaired functional responses. Recently research has highlighted the importance of NK cell metabolism in facilitating robust NK cell effector functions. This article will discuss our current understanding of murine and human NK cell metabolism and the key signalling pathways that med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
303
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(310 citation statements)
references
References 100 publications
7
303
0
Order By: Relevance
“…It serves as a further example to the power of studying single-cell heterogeneity within seemingly homogenous populations (here, Th17n), which allowed us to identify a novel regulator that would have otherwise been missed at a population level (here, a comparison of Th17p and Th17n). The computational prediction and the data corroborating it also demonstrate that despite the common assumption that glycolysis promotes proinflammatory functions in Th17 cells and other immune compartments [2], [3], [83]- [87], the role of glycolysis in induction of pro-inflammatory phenotypes may more nuanced [88], [89].…”
Section: Discussionsupporting
confidence: 56%
“…It serves as a further example to the power of studying single-cell heterogeneity within seemingly homogenous populations (here, Th17n), which allowed us to identify a novel regulator that would have otherwise been missed at a population level (here, a comparison of Th17p and Th17n). The computational prediction and the data corroborating it also demonstrate that despite the common assumption that glycolysis promotes proinflammatory functions in Th17 cells and other immune compartments [2], [3], [83]- [87], the role of glycolysis in induction of pro-inflammatory phenotypes may more nuanced [88], [89].…”
Section: Discussionsupporting
confidence: 56%
“…Both DC and NK cells require c-Myc for metabolic reprogramming with activation, but HIF-1α dependency is stimuli-dependent for NK cells. 243 NK cell activation, via natural killer receptor (NKR) stimulation, required increased glycolysis. By contrast, IL-12 and IL-18 combined initiated IFN-γ production without increasing glycolysis or OXPHOS, and prolonged IL-15 treatment bypassed the glycolytic requirement for NKR-mediated activation.…”
Section: Natural Killer Cell Metabolismmentioning
confidence: 99%
“…244 As with other immune cells, mTOR is considered an important regulator of NK metabolic reprogramming, and mTORC1 is linked to NK maturation and activation. 243,245 Productive IAV infection of epithelial cells induced PI3K/mTOR/Akt signaling, resulting in mTORC1 directly phosphorylating S6 kinase, thereby activating a translational regulator that increases mRNA biogenesis, translational initiation, and elongation. 28 However, NK cell activation activated mTORC1 independent of PI3K-Akt through nutrient sensing and sterol regulatory element-binding protein (SERBP) activation.…”
Section: Il-15 Signaling In Nk Cells Was Concentration-dependent Lowmentioning
confidence: 99%
“…Scatter has been used as an indicator of metabolic alteration in NK cells (Castro et al, 2018) and we found that side scatter increased in NK cells from the livers of obese mice ( Figure 5a). NK cells use mTOR for nutrient sensing and it also has an important role in immune regulation (O'Brien and Finlay, 2019). The phosphorylation of ribosomal S6 protein (pS6) is used as an indicator of mTORC1 signaling and we found that pS6 was increased in NK cells freshly isolated from the livers of obese compared to lean mice (Figure 5b).…”
Section: Nk Cells In Obese Mice Are Metabolically Reprogrammedmentioning
confidence: 87%
“…NK cell-derived ILC1-like cells in tumors produce angiogenic and growth factors (Gao et al, 2017), so it is tempting to speculate that the ILC1-like cells we see emerging from the NK cell population in the obese liver may have a similar reparative effect. It has been suggested that NK cell metabolism could be targeted to prevent cancer (O'Brien and Finlay, 2019). In the light of recent findings that NK cells are less cytotoxic in obesity, and that this is at least partially mediated by metabolic changes, it might be tempting to consider using such treatments as a way to break the well-established link between cancer and obesity (Park et al, 2014).…”
Section: Discussionmentioning
confidence: 99%